2010
DOI: 10.1016/j.schres.2010.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and genetic factors in familial schizophrenia associated with the NOS1AP gene

Abstract: There is some evidence that childhood adversity may be associated with the expression of schizophrenia but whether genetic risk affects this finding is unknown. We investigated the history of early trauma in 194 subjects from 24 multiply affected families where schizophrenia was previously shown to be associated with a functional allele in the NOS1AP gene. In subjects with schizophrenia (n=79), only events prior to the onset of psychosis were considered. Generalized estimating equation models that adjusted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
3
25
0
1
Order By: Relevance
“…To this end, a Pub Med search was carried out using the keywords "(NOS1AP OR CAPON) AND schizophrenia" as well as "NOS1 AND schizophrenia", to identify all genetic studies on NOS1AP (n=24 retrieved studies) or NOS1 (n=42 retrieved) and schizophrenic disorders. Titles and abstracts were scrutinized to exclude non-genetic studies, reducing the number of included studies to Costain et al, 2010;Fang et al, 2008;Greenwood et al, 2011;Husted et al, 2010;Kremeyer et al, 2009;Miranda et al, 2006;Nicodemus et al, 2008;Wratten et al, 2009) and one on NOS1 (Fallin et al, 2005), presented family-based, but not case-control data and were therefore not integrated in the meta-analysis for methodological reasons. The remaining studies on NOS1AP (n=6; (Aberg et al, 2010;Delorme et al, 2010;Nicodemus et al, 2010;Puri et al, 2007;Puri et al, 2006;Zheng et al, 2005)) and NOS1 (n=14; (Cui et al, 2010;Donohoe et al, 2009;Kawohl et al, 2008;Nicodemus et al, 2010;O'Donoghue et al, 2012;Okumura et al, 2009;Reif et al, 2006;Reif et al, 2011;Riley et al, 2010;Rose et al, 2012;Shinkai et al, 2002;Silberberg et al, 2010;Tang et al, 2008;Wang et al, 2012)) reported on case-control association data and were scrutinized in greater detailed.…”
Section: Meta-analysismentioning
confidence: 99%
“…To this end, a Pub Med search was carried out using the keywords "(NOS1AP OR CAPON) AND schizophrenia" as well as "NOS1 AND schizophrenia", to identify all genetic studies on NOS1AP (n=24 retrieved studies) or NOS1 (n=42 retrieved) and schizophrenic disorders. Titles and abstracts were scrutinized to exclude non-genetic studies, reducing the number of included studies to Costain et al, 2010;Fang et al, 2008;Greenwood et al, 2011;Husted et al, 2010;Kremeyer et al, 2009;Miranda et al, 2006;Nicodemus et al, 2008;Wratten et al, 2009) and one on NOS1 (Fallin et al, 2005), presented family-based, but not case-control data and were therefore not integrated in the meta-analysis for methodological reasons. The remaining studies on NOS1AP (n=6; (Aberg et al, 2010;Delorme et al, 2010;Nicodemus et al, 2010;Puri et al, 2007;Puri et al, 2006;Zheng et al, 2005)) and NOS1 (n=14; (Cui et al, 2010;Donohoe et al, 2009;Kawohl et al, 2008;Nicodemus et al, 2010;O'Donoghue et al, 2012;Okumura et al, 2009;Reif et al, 2006;Reif et al, 2011;Riley et al, 2010;Rose et al, 2012;Shinkai et al, 2002;Silberberg et al, 2010;Tang et al, 2008;Wang et al, 2012)) reported on case-control association data and were scrutinized in greater detailed.…”
Section: Meta-analysismentioning
confidence: 99%
“…Individuals with severe mental illness (SMI) report elevated rates of traumatic experiences compared to the general population (Spidel et al, 2010) with estimates of lifetime interpersonal trauma exposure ranging between 16% and 98% (Morgan and Fisher, 2007;Husted et al, 2010;Bebbington et al, 2011;Subica et al, 2012). Trauma has been associated with more complex presentations and poorer prognoses among persons with SMI (Alvarez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The risk for developing SMI increases up to 33% following childhood abuse (Kessler et al, 2010) and this significant role of childhood abuse remains even after controlling for the presence of psychiatric illness in the parent (Husted et al, 2010). A meta-analysis of 10 prospective studies indicates that exposure to childhood abuse significantly increases the risk for the development of psychosis (Varese et al, 2012).…”
Section: Introductionmentioning
confidence: 99%